Anti‐Tubercular Insights of Carbolines – A Decade Critique. Issue 9 (4th March 2021) - Tewari, Upasana; Sharma, Divya; Srivastava, Shrey; Kumar, Banoth Karan; Faheem,; Murugesan, Sankaranarayanan
Abstract: Tuberculosis is one of the top 10 leading causes of death worldwide and is caused by the bacteria "Mycobacterium tuberculosis." The medications used to treat tuberculosis have many deficiencies, including long‐term treatment, expensive medications, etc. The continuing emergence of multidrug resistance (MTR) remains a critical health issue that needs to be tackled urgently. Increased HIV/AIDS co‐infection with tuberculosis has also worsened the condition. Carbolines, nitrogen‐containing tricyclic Compounds have a significant role in medicinal chemistry because of their broad pharmacological properties, such as anti‐tubercular, anti‐bacterial, anti‐leishmanial, anti‐cancer, anti‐viral, etc. A brief description of the anti‐tubercular ability of a diverse set of carbolines collected from the past ten years focused on synthetic procedures, structural‐activity relationship studies, and their molecular mechanism of action was clearly described in the current review. Abstract : Tuberculosis, the top 10 leading causes of death worldwide, is caused by the bacteria "Mycobacterium tuberculosis." There are a significant number of shortcomings in the treatment of tuberculosis. More and more tuberculosis co‐infections like HIV/AIDS have also deteriorated the disease. Carbolines, nitrogen‐containing tricyclic Compounds, have a significant role in medicinal chemistry because of their broad pharmacological properties, such as anti‐tubercular, anti‐bacterial, anti‐leishmanial, anti‐cancer, anti‐viral, etc. The literature investigation clearly articulated a short description of the anti‐tubercular capabilities of various Carbolines accumulated over the past ten years, concentrated on Synthetic methods, Structural Activity Relationship Studies, and their molecular mechanism of action.